Fine Root Seasonal Dynamics, Plasticity, and Mycorrhization in 2 Coexisting Mediterranean Oaks with Contrasting Aboveground Phenology - Coll, Lluís; Camarero, Araid; Aragón, Juan Martínez De; Camarero, Jesús Julio; Martínez de Aragón, Juan; Camarero, Araid; Aragón, Juan Martínez De (Ecoscience, 2012)
To advance understanding of the mechanisms underpinning the coexistence of Mediterranean oak species, we conducted a year-long analysis of the production, architecture, and mycorrhization status of the fine roots of a mixed evergreen (Quercus ilex) and winter deciduous (Quercus faginea) oak stand. We used the ingrowth bag technique to sample the fine roots produced by each species in spring, summer, and winter. For each season, root architecture traits (specific root length, root diameter, root tips) and variables associated to root ectomycorrhizal status were measured in the laboratory. Results showed a marked seasonality in the fine root architecture, including more fine root tips and longer roots per unit of weight formed in spring and summer, revealing a capacity in Mediterranean oak species to modify root architecture in spring and suggesting the possibility of increased resource capture in summer. Fine root ectomycorrhizal status was comparable between species and also showed marked seasonality: we found a high percentage of roots colonized by dead ectomycorrhizas in winter but low ectomycorrhizal colonization rates in summer. Quercus ilex produced greater amounts of fine roots than Q. faginea (particularly during spring), suggesting greater competitive ability in the former species for belowground resources.
Keywords: architecture et le statut; Chênes; coexistence d; des mécanismes supportant la; Ectomycorrhizae; espèces méditerranéennes de; et caduques; feuilles persistantes; fine roots; l; mixte de chênes à; mycorhizien des radicelles d; nous avons analysé sur; nous avons utilisé la; Phenology; pour accroître notre compréhension; Quercus faginea; Quercus ilex; résumé; root traits; technique du sac; un peuplement; une année la production

Photoprotection mechanisms in Quercus ilex under contrasting climatic conditions - Camarero, Jesús Julio; Olano, José Miguel; Arroyo Alfaro, Sandra Jackeline; Fernández-Marín, Beatriz; Becerril, José Maria; García-Plazaola, José Ignacio (Flora - Morphology, Distribution, Functional Ecology of Plants, 2012)
Acclimation to local conditions may produce adaptive responses in plants subjected to diverse climatic stresses. However, it has not been assessed how local adaptation and phenotypic plasticity contribute to photoprotection mechanisms in response to contrasting climatic conditions in Mediterranean tree species. We analyzed photoprotectionmechanisms inmature trees oftheMediterranean evergreen oak Quercus ilex at three sites with contrasting climatic conditions, i.e. xeric, continental and mesic sites. We studied morphological and physiological parameters indicative of photoprotection in adult trees in the ﬁeld. In order to establish whether these parameters were genetically determined we compared adults with seedlings germinated from acorns of the three sites and grown under common greenhouse conditions. In the ﬁeld we found no signiﬁcant differences in most of the physiological parameters in summer, but in winter the adulttrees fromthe continental site were photoinhibited. In contrast,there were signiﬁcant differences between seedlings in most photoprotective parameters evaluated. Morphological traits such as trichome density and leaf reﬂectance differed between populations, both in ﬁeld-grown trees and in greenhouse-grown seedlings, being higher in all cases in plants from the xeric site than elsewhere. Our ﬁndings suggest the existence of constitutive differences in leaf photoprotection mechanisms among Q. ilex populations. These divergences may represent an inherent source for more stress tolerant ecotypes in the face of changing climatic conditions.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: ecotypes; Holm oak; Mediterranean; photoprotection; Trichomes

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Effects of a severe drought on Quercus ilex radial growth and xylem anatomy - Gil-Pelegrín, Eustaquio; Corcuera, Leyre; Camarero, Jesús Julio (Trees - Structure and Function, 2004)
We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981– 1997. The annual predicted hydraulic conductance (Kh) was calculated following Hagen-Poisseuille’s law. We compared the tree-ring width, vessel diameter and Kh of Q. ilex subsp. ballota and co-existing ring-porous oaks (Q. faginea, Q. pyrenaica) for a dry summer (1994) and a wet summer (1997). To evaluate the drought-resistance of xylem for Q. ilex subsp. ballota (dominant under continental conditions) and Q. ilex subsp. ilex (dominant in mild areas) we determined vulnerability curves. Dimensionless indices of internode length, tree-ring width, and vessel density were compared with climatic data (monthly total precipitation and mean temperature) using correlation analyses. Internode length, tree-ring width, Kh, and mean and maximum vessel diameter declined in 1994. According to vulnerability curves, Q. ilex subsp. ballota showed a greater drought resistance than Q. ilex subsp. ilex. During the year of growth, we found a positive influence of January and June–August precipitation on the internode length, tree-ring width, and vessel density. The response of Q. ilex subsp. ballota radial-growth to summer drought was comparable to that of Q. faginea latewood. Overall, growth and wood anatomy of Q. ilex subsp. ballota showed a plastic response to drought.
Keywords: cavitation; climate; Dendroecology; vulnerability curve; Xylem